Pengembangan Media Pembelajaran Berbasis Audio Visual Powtoon Pada Mata Pelajaran Ekonomi Dengan Materi Pertumbuhan Dan Pembangunan Ekonomi Kelas XI Di MA NW Sukamulia Lombok Timur - Sulastriani, Sulastriani; Utomo, Danang Prio; Jailani, Huzain (Alpatih Harapan Semesta, 2024)
The purpose of this research is to see the validity of the audio visual powtoon learning method in economics lessons for class XI at MA NW Sukamulia, East Lombok. This development research is a type of research with the ADDIE research model. The sample in this study was all class XI students with a large number of students, namely 24 students. The purpose of this study is to produce valid and good media in economics lessons for class XI MA NW Sukamulia, East Lombok. This instrument uses a response questionnaire and expert validation attachments. The data collection technique will be carried out by applying media, responses and validation is a questionnaire that has criteria with a 5-1 assessment scale. The data analysis technique is processed using the validation data analysis formula and response data analysis which have each assessment criterion, namely 100% -0%. Based on the application of audio-visual powtoon-based learning media, the results of media expert validation were obtained at 88%, which is a feasible category, material experts with results of 96% in a very feasible category, teacher responses to media with results of 84% with good criteria, and student responses obtained results of 91.87 with a very interesting and feasible category. From the results of the data above, the implications of this audio-visual powtoon-based learning media can be said to be feasible and good to be applied as a learning medium